China in Russia, Russia in China: ethnic aspect of migration between the two countries in the past and present. Issue 1 (2nd January 2016) - Kireev, Anton A.
Abstract : Mutual migrations between Russia and China have been going on for centuries and their intensity in the long-term scale is steadily increasing. Migration processes have a significant impact not only on bilateral political relations of Russia and China, but also on the internal ethnic structure of these complex nations. In his work, the author presents the main results of the empirical study of changes in the number and composition of Russian migrants in China and Chinese migrants in Russia, their organization, cultural features, and relations with the parent and the host nations for the past 400 years. Considering the communities of Russian and Chinese migrants in their present state, the author reveals their internal heterogeneity, the existence in them the components of the different ethno-social types. In conclusion, the article assesses the overall impact of migration processes on the ethnic composition and structure of the Russian and Chinese civil nations. According to the author, in spite of increased complexity of the ethnic composition of Russia and China, mutual migrations contributed rather to internal ethnic and cultural consolidation, strengthening the national identity of Russians and Chinese.